Modeling the Effect of Temperature on Membrane Response of Light Stimulation in Optogenetically-Targeted Neurons - Peixoto, Helton M.; Cruz, Rossana M. S.; Moulin, Thiago C.; Leão, Richardson N. (Frontiers in Computational Neuroscience, 2020)
Optogenetics is revolutionizing neuroscience but an often neglected effect of light stimulation of the brain is the generation of heat. In extreme cases, light-generated heat kills neurons but mild temperature changes alter neuronal function. In this work, we investigated heat transfer in brain tissue for common optogenetic protocols using the finite element method. We then modeled channelrhodopsin-2 in a single- and a spontaneous-firing neuron to explore the effect of heat in light stimulated neurons. We found that, at commonly used intensities, laser radiation considerably increases the temperature in the surrounding tissue. This effect alters action potential size and shape and cause increase in spontaneous firing frequency in a neuron model. However, the shortening of activation time constants generated by heat in the single firing neuron model produce AP failures in response to light stimulation. We also found changes in the power spectrum density and a reduction in the time required for synchronization in an interneuron network model of gamma oscillations. Our findings indicate that light stimulation with intensities used in optogenetic experiments may affect neuronal function not only by direct excitation of light sensitive ion channels and/or pumps but also by generating heat. This approach serves as a guide to design optogenetic experiments that minimize the role of tissue heating in the experimental outcome.